2005
DOI: 10.1001/archopht.123.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Ingress of India Ink Into the Anterior Chamber Through Sutureless Clear Corneal Cataract Wounds

Abstract: Background: Sutureless clear corneal cataract incisions may be associated with an increased risk of endophthalmitis.Objective: To assess the degree of ocular surface fluid ingress into the anterior chamber of cadaveric human globes with clear corneal wounds. Methods: Self-sealing clear corneal incisions were created in 4 eyes, and intraocular pressure was controlled with an infusion cannula. To evaluate possible flow of surface fluid through the corneal wound, india ink was applied to the corneal surface while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 37 publications
2
71
0
Order By: Relevance
“…It has been shown in human cadaveric eyes that fluctuations of intraocular pressure following sutureless clear corneal cataract surgery may allow the entry of surface fluid into the anterior chamber during the initial postoperative period when the wound has not healed [6]. Postoperative hypotony and leakage after 25-gauge sutureless vitrectomy are potential risks, but in our case IOP was normal on postoperative day 1 and there was no leakage clinically.…”
Section: Discussionmentioning
confidence: 53%
“…It has been shown in human cadaveric eyes that fluctuations of intraocular pressure following sutureless clear corneal cataract surgery may allow the entry of surface fluid into the anterior chamber during the initial postoperative period when the wound has not healed [6]. Postoperative hypotony and leakage after 25-gauge sutureless vitrectomy are potential risks, but in our case IOP was normal on postoperative day 1 and there was no leakage clinically.…”
Section: Discussionmentioning
confidence: 53%
“…2 For instance, in human cadaveric eyes, fluctuations of IOP following sutureless clear cornea surgery may allow entry of surface fluid into the anterior chamber during the initial postoperative period when the wound has not healed. 17 Furthermore, with the 25-gauge vitrectomy system, the infusion flow rate is reduced sixfold, 1 potentially decreasing the amount of fluid that dilutes or flushes out organisms within the eye.…”
Section: Resultsmentioning
confidence: 99%
“…The healthy anterior segment is usually able to handle this contamination, however, and no infection occurs in most cases. Taban et al [5] have recently demonstrated, by use of a laboratory model, that clear corneal incisions may behave as valves during intraocular pressure fluctuations, enabling fluid from the ocular surface to enter and possibly contaminate the eye postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data [5] suggest, however, that clear corneal incisions may enable influx of ocular surface fluid thus enabling pathogens to gain entry into the anterior chamber postoperatively. Although these are plausible means of developing endophthalmitis, lack of wound integrity resulting in microleaks after sutureless incisions may also be an important factor that requires further investigation.…”
Section: Introductionmentioning
confidence: 99%